2016
DOI: 10.1017/sjp.2016.41
|View full text |Cite
|
Sign up to set email alerts
|

Rumination in Adolescence: the Distinctive Impact of Brooding and Reflection on Psychopathology

Abstract: Rumination has a crucial role in the onset, severity and maintenance of depression in adolescent and adult populations. The Ruminative Responses Scale (RRS) is the most widely self-report instrument used to assess individual differences in the tendency to engage in ruminative responses style. This paper aims to test the factor structure of the 10-item RRS and the gender-based measurement invariance, in a community sample of adolescents, using a Confirmatory Factor Analysis. Participants were 542 adolescents (5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 34 publications
1
13
1
Order By: Relevance
“…Cronbach’s α coefficients in our study were 0.75 for total scale and ranged from 0.61 to 0.70 for two sub-scales, which were little lower than those in previous studies [3, 15, 16, 18, 19]. Noteworthily, there are only 5 items in each factor, and the sample size was large, both of which would bring a lot of uncontrollable factitious factors.…”
Section: Discussioncontrasting
confidence: 67%
See 1 more Smart Citation
“…Cronbach’s α coefficients in our study were 0.75 for total scale and ranged from 0.61 to 0.70 for two sub-scales, which were little lower than those in previous studies [3, 15, 16, 18, 19]. Noteworthily, there are only 5 items in each factor, and the sample size was large, both of which would bring a lot of uncontrollable factitious factors.…”
Section: Discussioncontrasting
confidence: 67%
“…Brooding rumination refers to “mood pondering” (e.g., “I think why can’t I handle things better?”), whereas reflective rumination describes thoughtful and non-emotional reassessment of past and present events, feelings, and behaviors (e.g., “write down what you are thinking, and analyze it”) [ 12 ]. Using the simplified scale and eliminating the influence of the depression factor of RRS, researchers did find the scores of RRS-10 were better demonstrated the relationship between rumination and depression [ 13 15 ]. The RRS-10 had been reported to have good psychometric properties in both English-speaking and non-English speaking countries, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…In the original version, the Cronbach's alpha for brooding subscale was .77 (Treynor et al, 2003). This subscale also had adequate internal consistency in adolescents' sample (α = .80; Xavier et al, 2016b). In the current study the brooding subscale presented a Cronbach's alpha of .80.…”
Section: Methodsmentioning
confidence: 92%
“…Compared to the USA, Europe, Korean and Japan (Shin et al, 2015, Xavier et al, 2016Lee & Kim, 2014;Extremera & Fernandez-Berrocal, 2006), the Cronbach's alpha of this study may be somewhat lower but acceptable according to standards of Baker et al (Lee & Kim, 2014). Moreover, compared with college students samples (Lei et al, 2017), the application of RRS on adolescents samples showed higher Cronbach's alpha of the total scale.…”
Section: Discussionmentioning
confidence: 48%